2023
DOI: 10.1017/pds.2023.386
|View full text |Cite
|
Sign up to set email alerts
|

Vr or Not? Investigating Interface Type and User Strategies for Interactive Design Space Exploration

Abstract: Computational design tools allow the generation of vast numbers of possible designs, entrusting the human designer with describing constraints or specifications to guide exploration of the design space. Designers can have many different decision considerations when conducting this type of exploration, including form, function, users, or context. In this work, we investigate strategies that emerge when people are tasked with exploring a large design space within either a non-immersive (2D) or immersive (VR) int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Seybold and Mantwill (2021) examined 3D sketching in VR and observed that the same solution quality can be obtained using VR while achieving faster development times. Nandy et al ( 2023) investigated the design space across immersive and non-immersive interfaces using pre-designed design elements. They found that 2D interface for modelling enabled users to explore a larger range of designs, whereas VR was more useful in exploring the advantages and disadvantages of single-design solutions.…”
Section: Vr-based Modelling and Editingmentioning
confidence: 99%
“…Seybold and Mantwill (2021) examined 3D sketching in VR and observed that the same solution quality can be obtained using VR while achieving faster development times. Nandy et al ( 2023) investigated the design space across immersive and non-immersive interfaces using pre-designed design elements. They found that 2D interface for modelling enabled users to explore a larger range of designs, whereas VR was more useful in exploring the advantages and disadvantages of single-design solutions.…”
Section: Vr-based Modelling and Editingmentioning
confidence: 99%
“…While the merging of physical and digital into a single interface is well-studied, the recent maturation of MR-capable technologies has enabled their application in domains ranging from education (Hallmann et al, 2023), to architecture (Kim and Hyun, 2022), to design (Verlinden and Horváth, 2009). Several works have highlighted the importance of the viewing interface for design performance (Berni et al, 2023;Horvat et al, 2022;Nandy et al, 2023) noting differences when using XR compared to traditional modes. Benefits of XR implementation for design have been shown to be broad, including enhanced spatial reasoning (Horvat et al, 2022), divergence (Sopher et al, 2022), confidence and satisfaction with outcomes (Kim and Hyun, 2022), and collaboration (Bisson et al, 2023).…”
Section: Extended Reality Technologies In Designmentioning
confidence: 99%
“…References for works: A(Scurati et al, 2023), B(Hu et al, 2023), C(Latif et al, 2023), D(Trump and Shealy, 2023), E(Nanjappan et al, 2023), F(Steinhauser et al, 2023), G(Horvat et al, 2022), H(Berni et al, 2023), I(Nandy et al, 2023), J(Hireche et al, 2023), K(Bisson et al, 2023), L(Hallmann et al, 2023), M(Harlan et al, 2023), N(Brunzini et al, 2021), O(Yengui and Stechert, 2021), P(Seybold and Mantwill, 2021), Q(Porro et al, 2022), R(Goethem et al, 2021), S(Mariani et al, 2021), T(Romero et al, 2021), U(Kujur et al, 2022), V(Melo et al, 2022) 3 See https://tinyurl.com/DMFdrill, https://tinyurl.com/DMFcontroller, https://dmf-lab.co.uk/our-lab/…”
mentioning
confidence: 99%
“…However, due to the particularity of virtual reality technology, traditional human-computer interaction methods may not be fully applicable to virtual reality environments (Nandy et al, 2023). For example, the traditional way of mouse and keyboard interaction may not be intuitive and natural enough in a VR environment.…”
Section: Design Principles Of Virtual Reality Interactive Interfacesmentioning
confidence: 99%